Two new species, Begonia minhaniae and B. dieuanhiae (sect. Platycentrum, Begoniaceae), from northwestern Vietnam - Hoang, Thanh Son; Lin, Che-Wei (Phytotaxa, 2022)
Two novel species in Begonia sect. Platycentrum from northwestern Vietnam, B. minhaniae and B. dieuanhiae, are described and illustrated. Both species superficially resemble B. phouchomvoyensis in their rhizomatous habit, plain green ovary and leaves, 4-tepaled staminate flowers and 3-locular ovaries, but they can be clearly distinguished from the latter by several morphological characters such as morphology of vestiture, fewer anthers (those of B. minhaniae are ca. 15 vs. ca. 45 in B. phouchomvoyensis) and more tepals of pistillate flower (5 tepals in B. dieuanhiae vs. 3 tepals in B. phouchomvoyensis). These two novel discoveries highlight the growing body of research showing the rich and varied biodiversity of Begonia in the flora of Vietnam.